Significant effects on sharing class notes and materials using Study Jom application among students - Ghazali, Mazlinah; Idris, Mohd Norhaedir; Ruslan, Rohayah; Ahmad, Siti Hawa; Basharudin, Azmi (Centre of Foundation Studies, IIUM, 2023)
Good class notes and materials are compulsory for students to achieve good academic results online or offline. Often study guidelines do not match with lectures, suggesting students should take notes selectively and concisely. Effective note-taking is about summarising core concepts as accurately as possible in students' own words, connecting those concepts to other ideas within and between lectures, and capturing questions that arise for improved understanding and clarity. Handwritten notes to record lessons learnt in class are more impactful in strengthening the learning effect. Without class notes, absent students will lose focus in class and later be left out. Students need well-written class notes and other materials to understand the teaching from their lecturers. However, getting good class notes from friends who attended the classes is not always possible. Thus, the students will hardly perform in their studies. About ten students were interviewed as a preliminary study on how vital class notes are and their means of getting them. Most of them admitted the difficulties in getting the class notes. Therefore, a web-based application called Study Jom was developed to help students reach their class notes and materials quickly, efficiently, and systematically. Students were given access to Study Jom to experience it before answering a semi-structured feedback survey for analysis. The findings capture positive feedback and experience among students in getting better class notes and study materials using this app. In future, Study Jom is expected to expand with more features to enable the search across more faculties and universities.